2019
DOI: 10.5194/isprs-archives-xlii-2-w15-1157-2019
|View full text |Cite
|
Sign up to set email alerts
|

Videogrammetry vs Photogrammetry for Heritage 3d Reconstruction

Abstract: <p><strong>Abstract.</strong> In the last years we are witnessing an increasing quality (and quantity) of video streams and a growing capability of SLAM-based methods to derive 3D data from video. Video sequences can be easily acquired by non-expert surveyors and possibly used for 3D documentation purposes. The aim of the paper is to evaluate the possibility to perform 3D reconstructions of heritage scenarios using videos ("videogrammetry"), e.g. acquired with smartphones. Video frames are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In light of the recent developments in other similarly low-to-medium cost and nearreal time sensors (Wang et al, 2020), it is interesting to see how smartphone videogrammetry fares for the specific context of heritage documentation. A similar study was conducted by Torresani and Remondino (2019) in which the authors concluded that it is theoretically viable to use smartphone videogrammetry to generate 3D records for heritage objects, although they maintained that traditional photogrammetry is still irreplaceable for higher-precision requirements.…”
Section: Introductionmentioning
confidence: 91%
“…In light of the recent developments in other similarly low-to-medium cost and nearreal time sensors (Wang et al, 2020), it is interesting to see how smartphone videogrammetry fares for the specific context of heritage documentation. A similar study was conducted by Torresani and Remondino (2019) in which the authors concluded that it is theoretically viable to use smartphone videogrammetry to generate 3D records for heritage objects, although they maintained that traditional photogrammetry is still irreplaceable for higher-precision requirements.…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, the user, while capturing the video, does not know if he/she has made any rapid movement that could have caused the continuity of the trajectory to be lost or if he/she has made any other movement with the camera that cannot be resolved later with photogrammetry (for example, camera autorotations without displacement of the centre of projection) (Luhmann et al 2006). And finally, the frame selection must be optimal to achieve the best results, avoiding excesses or defects in the number of images that may cause inaccuracies or, simply, a lack of sufficient connection between the images causing a break in the formation of the trajectory, considering the form of continuous capture that the video has (Torresani y Remondino 2019).…”
Section: Manuscriptmentioning
confidence: 99%
“…Videogrammetry for this type of capture requires, therefore, a process of extraction and selection of frames for the subsequent photogrammetric process. The methodology for selecting keyframes from among all the frames generated by the video can be divided into three types (Ortiz-Coder and Sánchez-Ríos, 2020;Torresani and Remondino, 2019):…”
Section: Videogrammetrymentioning
confidence: 99%